Effect of Changes in Dissolved Oxygen Concentrations on the Spatial Dynamics of the Gulf Menhaden Fishery in the Northern Gulf of Mexico. Issue 1 (30th October 2014) - Langseth, Brian J.; Purcell, Kevin M.; Craig, J. Kevin; Schueller, Amy M.; Smith, Joseph W.; Shertzer, Kyle W.; Creekmore, Sean; Rose, Kenneth A.; Fennel, Katja
Abstract: Declines in dissolved oxygen (DO) concentrations in aquatic environments can lead to conditions of hypoxia (DO ≤ 2 mg/L), which can directly and indirectly affect aquatic organisms. Direct effects include changes in growth and mortality; indirect effects include changes in distribution, movement, and interactions with other species. For mobile species, such as the pelagic filter‐feeding Gulf Menhaden Brevoortia patronus, indirect effects are more prevalent than direct effects. The northern Gulf of Mexico experiences one of the largest areas of seasonal hypoxia in the world; this area overlaps spatially and temporally with the Gulf Menhaden commercial purse‐seine fishery, which is among the largest fisheries by weight in the United States. Harvest records from the Gulf Menhaden fishery in 2006–2009 and fine‐scale spatial and temporal predictions from a physical–biogeochemical model were used with spatially varying regression models to examine the effects of bottom DO concentration, spatial location, depth, week, and year on four response variables: probability of fishing, total Gulf Menhaden catch, total fishery effort, and CPUE. We found nearshore shifts in the probability of fishing as DO concentration declined, and we detected a general westward shift in all response variables. We also found increases in CPUE as DO concentration declined in the Louisiana Bight, an area that experiences chronic, severe hypoxia. The overall effects of environmental conditions on fishing response variables appeared to be moderate. Nevertheless, movement of either Gulf Menhaden or the purse‐seine fishery in response to environmental conditions could potentially affect the susceptibility of Gulf Menhaden to harvest and could therefore influence assessment of the stock and associated stock status indicators. Received March 4, 2014; accepted June 26, 2014